Components of Variance for Some Economic Traits among Rhode Island Chicken Bred in the Northern Guinea Savanna Zone of Nigeria - Adeyinka, I.A.; Oni, O.O.; Nwagu, B.I.; Adeyinka, F.D. (International Journal of Poultry Science, 2006)
The data used to calculate the variance components of various production traits was obtained from records of about 4000 hens daughters of about 180 cocks mated to about 1,500 dams and collected over 5 year period. Two strains of Rhode Island Chickens were involved in this study. Within the red strain population sire`s contribution to total variation in age at first egg did not exceed 8.6% across the year and 6.9% in the white strain. Except for body weight at 40 weeks of the red strain where the contribution of the sire exceed 14%, the contribution of the sire to the total variation for all the economic traits considered in this study were generally low for both strain of the layer type chickens under consideration. Generally dam component of variance were higher most of the time and in many traits within the red strain population.